THE IDEOLOGICAL AND THEMATIC ANALYSIS OF KOKASH (KARASAI) ESENGELDYULY’S (1840–1923) DIDACTIC POEM DÜNIE ÜŞIN ĞIBRATNAMA (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
In the context of globalization, the study of the national spiritual heritage, including the scholarly reinterpretation of moral and ethical values reflected in traditional literature, has become increasingly important. In this regard, the study of the literary legacy of Kokash (Karasai) Esengeldyuly, a Kazakh poet who lived in the late nineteenth and early twentieth centuries, represents one of the significant issues in Kazakh literary studies. The purpose of this article is to determine the place of the poem Dünie üşin Ğibratnama (“Admonition for the World”) in the history of Kazakh literature through a comprehensive analysis of its ideological and thematic content, worldview foundations, artistic system, and educational and didactic significance. The research employs historical-functional, hermeneutic, and comparative-historical methods. The poem is examined from the perspective of the traditional Kazakh worldview, Islamic values, Sufi teachings, and national moral and ethical principles. The findings demonstrate that the ideological basis of the work lies in the continuity between Islamic thought and the traditions of Kazakh poetic literature. Furthermore, the study systematically analyzes the themes of morality, spirituality, the transience of worldly life, the meaning of human existence, and spiritual perfection, substantiating their educational and enlightening significance for contemporary society. The results contribute to a broader integration of Kokash Esengeldyuly’s literary heritage into academic discourse, deepen the understanding of the religious and didactic tradition in Kazakh literature, and promote further comprehensive research into the national literary heritage.